More quick team-building activities for busy managers : 50 new exercises that get results in just 15 minutes - Miller, Brian Cole, 1956- (AMACOM/American Management Association, 2007)
For anyone charged with the task of bringing teams together, More Quick Team-Building Activities for Busy Managers is the answer. Without any expensive training or previous experience, this book provides quick, easy, and effective activities for new teams to spark creativity, deal with change, improve communication, and much more.